Alkaline Technosol contaminated by former mining activity and its culturable autochthonous microbiota - Šimonovičová, A; Ferianc, P; Vojtková, H; Pangallo, D; Hanajík, P; Kraková, L; Feketeová, Z; Čerňanský, S; Okenicová, L; Žemberyová, M; Bujdoš, M; Pauditšová, E (Chemosphere, 2017)
Technosols or technogenic substrates contaminated by potentially toxic elements as a result of iron mining causes not only contamination of the surrounding ecosystem but may also lead to changes of the extent, abundance, structure and activity of soil microbial community. Microbial biomass were significantly inhibited mainly by exceeding limits of potentially toxic metals as arsenic (in the range of 343-511 mg/kg), copper (in the range of 7980-9227 mg/kg), manganese (in the range of 2417-2670 mg/kg), alkaline and strong alkaline pH conditions and minimal contents of organic nutrients. All of the 14 bacterial isolates, belonged to 4 bacterial phyla, Actinobacteria, Firmicutes; β- and γ-Proteobacteria. Thirteen genera and 20 species of microscopic filamentous fungi were recovered. The most frequently found species belonged to genera Aspergillus (A. clavatus, A. niger, A. flavus, A. versicolor, Aspergillus sp.) with the dominating A. niger in all samples, and Penicillium (P. canescens, P. chrysogenum, P. spinulosum, Penicillium sp.). Fungal plant pathogens occurred in all surface samples. These included Bjerkandera adustata, Bionectria ochloleuca with anamorph state Clonostachys pseudochloleuca, Lewia infectoria, Phoma macrostoma and Rhizoctonia sp.
Keywords: houby; mangan; Soil Microbiology; látky znečišťující půdu; Autochthonous isolates; Copper; Bacteria; Potentially toxic elements; Alkaline Technosols; měď; Manganese; Fungi; Arsenic; Microbiota; mikrobiota; Mining; Soil Pollutants; půdní mikrobiologie; hornictví; Biomass; arsen; Microbial biomass; biomasa